The effect of remimazolam-based total intravenous anesthesia versus sevoflurane-based inhalation anesthesia on emergence delirium in children undergoing tonsillectomy and adenoidectomy: study protocol for a prospective randomized controlled trial - Ma, Hong-Yu; Cai, Yu-Hang; Zhong, John Wei; Chen, Jia; Wang, Zhen; Lin, Chao-Yi; Wang, Qiao-Qiao; Liu, Hua-Cheng (Frontiers in Pharmacology, 2024)
Background: Remimazolam, a new ultrashort-acting benzodiazepine, is becoming increasingly applied in general anesthesia. This study is designed to investigate the effect of remimazolam-based total intravenous anesthesia and sevoflurane-based inhalation anesthesia on emergence delirium in pediatric tonsillectomy and adenoidectomy.Methods and analysis: This is a monocentric, prospective, randomized, double-blind clinical trial. A total of 90 pediatric patients will be randomized to receive remimazolam-based total intravenous anesthesia (remimazolam group, n=45) or sevoflurane-based inhalation anesthesia (sevoflurane group, n=45). The primary outcome will be the incidence of emergence delirium, which will be evaluated using pediatric anesthesia emergence delirium scale (PAED). The secondary outcomes will include the extubation time, recovery time, behavior change using the posthospitalization behavior questionnaire for ambulatory surgery (PHBQ-AS) and adverse events. Ethics and dissemination: This study has been approved by the Institutional Review Board (IRB) of the Second Affiliated Hospital and Yuying Children's Hospital of Wenzhou Medical University (2023-K-262-02).